Introduction - Laurent Mellet (Études Britanniques Contemporaines, 2019)
This issue gathers a series of articles which explore the validity of the concept of ‘narrative democracy’ when trying to unveil the narrative, aesthetic and ethical specificities of 20th- and 21st-century British literature and visual arts. These articles show how the concept may lead to a new critical perspective on the way these works are premised on a particular apprehension of individual experience and of its narrative, turning the latter and the work itself into forms producing commonality.